Biomaterials in fetal surgery. (17th May 2019) - Winkler, Sally M.; Harrison, Michael R.; Messersmith, Phillip B.
Abstract : Biomaterials have already improved fetal surgery outcomes, and biomaterials engineers have a unique opportunity to help make fetal surgery safer and more effective. Abstract : Fetal surgery and fetal therapy involve surgical interventions on the fetus in utero to correct or ameliorate congenital abnormalities and give a developing fetus the best chance at a healthy life. Historical use of biomaterials in fetal surgery has been limited, and most biomaterials used in fetal surgeries today were originally developed for adult or pediatric patients. However, as the field of fetal surgery moves from open surgeries to minimally invasive procedures, many opportunities exist for innovative biomaterials engineers to create materials designed specifically for the unique challenges and opportunities of maternal–fetal surgery. Here, we review biomaterials currently used in clinical fetal surgery as well as promising biomaterials in development for eventual clinical translation. We also highlight unmet challenges in fetal surgery that could particularly benefit from novel biomaterials, including fetal membrane sealing and minimally invasive myelomeningocele defect repair. Finally, we conclude with a discussion of the underdeveloped fetal immune system and opportunities for exploitation with novel immunomodulating biomaterials.